Non-nicotine constituents in cigarette smoke extract enhance nicotine addiction through monoamine oxidase A inhibition - Liu, Guanglin; Wang, Ruiyan; Chen, Huan; Wu, Ping; Fu, Yaning; Li, Kaixin; Liu, Mingda; Shi, Zhihao; Zhang, Yuan; Su, Yue; Song, Lingxiao; Hou, Hongwei; et al. (Frontiers in Neuroscience, 2022)
Tobacco addiction has been largely attributed to nicotine, a component in tobacco leaves and smoke. However, extensive evidence suggests that some non-nicotine components of smoke should not be overlooked when considering tobacco dependence. Yet, their individual effect and synergistic effect on nicotine reinforcement remain poorly understood. The study herein focused on the role of non-nicotine constituents in promoting the effects of nicotine and their independent reinforcing effects. Denicotinized cigarettes were prepared by chemical extracting of cut tobacco, and the cigarette smoke extracts (CSE, used as a proxy for non-nicotine ingredients) were obtained by machine-smoking the cigarettes and DMSO extraction. The compositions of harmful components, nicotine, and other minor alkaloids in both cut tobacco and the CSE of experimental denicotinized cigarettes were examined by GC-MS, and compared with 3R4F reference cigarettes. individually and in synergy with nicotine were determined by conditioned place preference (CPP), dopamine (DA) level detection, the open field test (OFT), and the elevated plus maze (EPM). Finally, the potential enhancement mechanism of non-nicotinic constituents was investigated by nicotine metabolism and monoamine oxidase A (MAOA) activity inhibition in the striatum of mice and human recombinant MAOA. Thenicotine content in smoke from the experimental denicotinized cigarettes (under ISO machine-smoking conditions) was reduced by 95.1% and retained most minor alkaloids, relative to the 3R4F reference cigarettes. It was found that non-nicotine constituents increased acute locomotor activities. This was especially pronounced for DA levels in NAc and CPP scores, decreased the time in center zone. There were no differences in these metrics with DNC group when compared to the NS group. Non-nicotine constituents alone did not show reinforcing effects in CPP or striatum DA levels in mice. However, in the presence of nicotine, non-nicotine constituents further increased the reinforcing effects. Furthermore, non-nicotine constituents may enhance nicotine’s reinforcing effects by inhibiting striatum MAOA activity rather than affecting nicotine metabolism or total striatum DA content in mice. These findings expand our knowledge of the effect on smoking reinforcement of non-nicotine constituents found in tobacco products.